INCLUSIVE PARTICIPATORY APPROACHES ON CLIMATE ADAPTATION AND MITIGATION FOR FARMERS - Stormy Vertygo; Melinda R. S. Moata; Dina V. Sinlae; Noldin Abolla (Jurusan Peternakan Politeknik Pertanian Negeri Kupang, 2020)
Community service organized by Politani in the form of a Tailor-made Training (TMT) was conducted from 6th to 13th of October 2019 in Soe city and Noinbilla village, South Central Timor Regency (TTS). The aim of this training was to give a clear perspective and profound comprehension about inclusive participatory approaches on climate adaptation and mitigation especially for farmers which could subsequently assist them in establishing a smarter-climate agriculture that is more resilient to climate change. The program was divided into two major sessions: 1) In-door training; where the participants were given interactive-based theoretical training about the topic and 2) Study Filed Trip; where they visited several vegetational areas in order to further practised what they have learned from the previous session. Evaluation showed that almost all of the participants attending the program have had a clear understanding on the basic principles of smart-climate agriculture and how they are going to apply the participatory approaches for establishing and strengthening partnership form multi-sectoral perspectives in order to achieve a more climate-resilient agriculture yet still productive.